2014
DOI: 10.1007/s00114-014-1234-7
|View full text |Cite
|
Sign up to set email alerts
|

Do feather-degrading bacteria actually degrade feather colour? No significant effects of plumage microbiome modifications on feather colouration in wild great tits

Abstract: Parasites are known to exert selective pressures on host life history traits since the energy and nutrients needed to mount an immune response are no longer available to invest in other functions. Bird feathers harbour numerous microorganisms, some of which are able to degrade feather keratin (keratinolytic microorganisms) and affect feather integrity and colouration in vitro. Although named "feather-degrading" microorganisms, experimental evidence for their effects on feathers of free-living birds is still la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Microorganisms can significantly reduce the quality of feathers through feather degradation (Jacob, Colmas, Parthuisot, & Heeb, 2014;Leclaire, Pierret, Chatelain, & Gasparini, 2014;Ruiz-Rodríguez et al, 2009;Shawkey, Pillai, & Hill, 2009) and hence the flight ability of prey. Any such damage to the plumage would be selected against, with damage to the plumage reaching such extremes as complete degradation and hence disappearance of barbules, barbs, or even loss of entire segments of feathers (e.g., Kim, Lim, & Suh, 2001;Møller et al, 2013;Onifade, Al-Sane, Al-Musallam, & Al-Zarban, 1998;Ruiz-Rodríguez et al, 2009).…”
Section: Such Interactions Between Predators and Prey May Results In Cmentioning
confidence: 99%
“…Microorganisms can significantly reduce the quality of feathers through feather degradation (Jacob, Colmas, Parthuisot, & Heeb, 2014;Leclaire, Pierret, Chatelain, & Gasparini, 2014;Ruiz-Rodríguez et al, 2009;Shawkey, Pillai, & Hill, 2009) and hence the flight ability of prey. Any such damage to the plumage would be selected against, with damage to the plumage reaching such extremes as complete degradation and hence disappearance of barbules, barbs, or even loss of entire segments of feathers (e.g., Kim, Lim, & Suh, 2001;Møller et al, 2013;Onifade, Al-Sane, Al-Musallam, & Al-Zarban, 1998;Ruiz-Rodríguez et al, 2009).…”
Section: Such Interactions Between Predators and Prey May Results In Cmentioning
confidence: 99%
“…Investigating whether competitive interactions between microbes led to this intriguing result and to what extent feather microbiome regulation by birds might take part in it is required to develop our understanding of bird–microbiome interactions (Shawkey, Pillai & Hill ; Jacob et al . ,b).…”
Section: Discussionmentioning
confidence: 99%
“…; Morgan, Segata & Huttenhower ; Jacob et al . ,b), and our understanding of the relative effects of the various components of the microbiome on the birds is particularly limited. Here, we found that increasing nest bacterial densities and modifying the bacterial community composition, as produced in the TSB treatment, had no overall significant effect on egg compounds and nestling development.…”
Section: Discussionmentioning
confidence: 99%
“…), and the in vivo association between FDB and plumage condition is still largely unexplored (Gunderson , exceptions are Jacob et al . , Leclaire et al . ).…”
mentioning
confidence: 99%